Understanding Durban University of Technology Students' Perceptions of Biodiversity Loss - Jonathan Foley; Himansu Baijnath; Donal P. McCracken (Environmental Association of Southern Africa, 2018)
Biodiversity loss has been recognised as a global and local problem of increasing magnitude. As future leaders, university students may play an influential role in alleviating this serious and multifaceted problem. This particular research focuses on a relatively new area of study not yet covered in the literature, that of South African university students' perceptions and understandings of biodiversity. This paper seeks to describe the knowledge, attitudes and perceptions of students at Durban University of Technology towards biodiversity and to consider some of the socio-cultural causal factors. Student opinions were sampled using an appropriate survey modelled after European biodiversity surveys and adapted to meet the unique challenges of South African conditions and rich biodiversity found in Durban's urban green spaces. The quantitative data were then merged with qualitative data drawn from four focus groups sampled across selected faculties at the institution. The focus groups involved guided discussion on the relevance of biodiversity, viewing of video clips and local field visits to Pigeon Valley Nature Reserve and the Durban Botanic Gardens. The results indicated high levels of concern for biodiversity loss and strong cultural connections with traditional African medicinal plants.